Criteria for assessing action undertaken by border municipalities towards a “green smart city” - Łaźniewska, Ewa; Janicka, Izabela; Górecki, Tomasz (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
The article presents a proposal for a research tool that might assess the ecological activity of municipalities, with particular emphasis on those that lie on national boundaries. With climate change, it has become necessary to take into account the principles of sustainable growth while maintaining high living standards in the long term. Systematic research on the action undertaken by municipalities in this area is a necessary requirement in the coming years. For this reason, the main directions and areas of research in the process of approaching the concept of a “green smart city” have been outlined. The available literature is limited to research in the field of smart cities and examines solutions for large urban agglomerations. The evaluation criteria of “ecological maturity” proposed in this paper are designed for small border municipalities. One may accept the thesis that due to their specificity, location, natural diversity and the opportunities for cooperation with a foreign partner that they offer, border municipalities can create a model of ecological behaviour in terms of a “green smart city”. This evolution requires support and monitoring for policymakers, and the proposed online research tool may reveal “ecological immaturities”, decisional errors or just plain negligence. One might only hope that, as a result of these indications, the recommendations will prove valuable for all local government units. On the other hand, a number of doubts and dilemmas are raised that researchers are unable to eliminate at this stage.

Artykuł prezentuje propozycję narzędzia badawczego do oceny aktywności ekologicznej gmin ze szczególnym uwzględnieniem gmin przygranicznych. Wraz ze zmianami klimatu pojawiła się konieczność uwzględniania w dłuższej perspektywie czasu zasad zrównoważonego wzrostu z zachowaniem wysokich standardów życia. Systematyczne badanie aktywności gmin w tym zakresie to konieczny wymóg najbliższych lat. Z tego względu nakreślono główne kierunki i obszary badań w procesie dochodzenia do koncepcji „green smart city”. Dostępna literatura ogranicza się do badań w zakresie smart city i dotyczy rozwiązań dla dużych aglomeracji miejskich. Zaproponowane w pracy kryteria ewaluacyjne „dojrzałości ekologicznej” skierowane są do niewielkich przygranicznych gmin miejskich. Można przyjąć tezę, że gminy przygraniczne ze względu na swoją specyfikę, położenie, różnorodność przyrodniczą i możliwości kooperacyjne z partnerem zagranicznym mogą tworzyć model zachowań ekologicznych w aspekcie green smart city. Ewolucja ta wymaga wsparcia i monitoringu dla decydentów, a proponowane narzędzie badawcze dostępne online może wykazać „niedojrzałości ekologiczne”, błędy decyzyjne oraz zwykłe zaniedbania. Można mieć jedynie nadzieję, że w efekcie tych wskazań cenne okażą się rekomendacje dla wszystkich jednostek samorządowych. Z drugiej strony wzbudzają one szereg wątpliwości i dylematów, których badacze na tym etapie nie mogą wyeliminować.
Kryteria oceny aktywności gmin przygranicznych w kierunku „green smart city”
Keywords: sustainable development; smart city; ecology; cross-border green smart city; zrównoważony rozwój; smart city; ekologia; przygraniczne zielone smart city